Реконструкция структуры ядерного графита методами многоточечной статистики - Комир, Антон Игоревич (НТУ "ХПИ", 2016)
Представлен разработанный алгоритм реконструкции трехмерной структуры ядерного графита на основе металлографических изображений. В качестве модельного материала был использован ядерный графит марки АРВ. Проведен гистограммный и вариограммный анализ приведенной методики и отдельно алгоритма реконструкции двух- и трехмерных структур. Показано точность воспроизведения структуры – 4–5 % отклонения при реконструкции материала трехмерной структуры ядерного графита и 15 % отличие в коллинеарности структуры на расстояниях в половину размера реконструируемой структуры.

Presents the developed algorithm of a three-dimensional reconstruction the structure of nuclear graphite based on metallographic images using methods of multipoint statistic. Currently used algorithm SNESIM as method for formation 2D structures. As model material was used nuclear graphite grade ARV with porosity about 20 %. The histogrammic and variogram analysis of the given technique and separately algorithm of reconstruction two – and three-dimensional structures is carried out. It is shown the accuracy of reproduction of structure – 4–5 % the variation in the reconstruction of three-dimensional material structure of nuclear graphite and a 15 % difference in the collinear structure at distances of half the size of the reconstructed structure. Presented algorithm can be based on different methods of reconstruction 2D structure using hard data pointsand training image and used for reconstruction structure of different materials.
Reconstruction of nuclear graphite structure by multipoint statistics
Keywords: 3D реконструкция; металлографические изображения; гистограммный анализ; вариограммный анализ; sGems; 3D reconstruction